The effect of sildenafil on gastric motility and satiation in healthy controls. Issue 6 (1st July 2018) - Carbone, F; Tack, J
Abstract : Sildenafil induces relaxation of smooth muscle cells by blocking PDE5. Dyspepsia is one of sildenafil's most frequently reported adverse events, suggesting its effect on gastric motility. Our aim was to study the effect of sildenafil on gastric accommodation (GA) and gastric emptying (GE) in healthy volunteers (HVs). Methods: Sildenafil (50 mg) or placebo was randomly administered to 16 blinded HVs. After a manometry probe and an infusion catheter were positioned in the proximal stomach, the intragastric pressure (IGP) was measured before and during nutrient drink infusion (ND, 60 ml/min). HVs were asked to score their hunger, satiation and six epigastric symptoms at five‐minute intervals. The experiment ended when the HVs scored maximal satiation during ND infusion at one‐minute intervals. To assess GE, breath samples were collected every 15 minutes for six hours after the meal (244 kcal). Results: ND infusion induced a drop in proximal stomach IGP, which was suppressed by sildenafil (average area under the curve for sildenafil: −33.6 ± 8.8 mmHg; placebo: −60.8 ± 11.3 mmHg, p = 0.005). Sildenafil‐treated volunteers reached earlier maximal satiation compared to placebo (678 ± 70 ml vs. 836 ± 82.6 ml, p = 0.019). Finally, GE was significantly slower after sildenafil (90.6 ± 5.9 min vs. 76.6 ± 7.1 min, p = 0.04). Conclusion: Sildenafil inhibits GA, leading to significantly decreased nutrient tolerance, and slightly delays the GE rate in humans.